Simple Financial Management Training To Improve The Sustainability Of Small And Medium Enterprises In Kepuh Village, Pacarejo, Semanu, DIY - Norviana, Syahida; Ariyanto, Ardi; Ahmad, Entus Nuryana; Rachmawati, Indria Desy (Abdi Masyarakat, 2025)
This community service activity aims to improve the financial management capacity of MSMEs in Kepuh Hamlet, Gunungkidul through participatory training. The background of this activity is based on the finding that 85% of local MSME players still mix personal and business finances, which has the potential to hamper business development. The method used is a learning by doing approach with three main stages: interactive material presentation, hands-on practice in preparing financial reports, and participatory discussion. The evaluation results showed that 90% of participants (32 people) actively participated in all activity sessions, 85% of participants (30 people) were able to correctly make simple financial records, and 80% of participants (28 people) were able to clearly distinguish between personal and business expenses. Monitoring of implementation two weeks after the training showed that 70% of participants (25 people) consistently applied the financial recording system they had learned. This activity successfully addressed the issue of MSMEs through a practical approach that was appropriate for the characteristics in Kepuh Village.